Reframing gender in rural tourism: a cross-national analysis of official websites in the Mekong Subregion - Hoang, Mi; Le Minh, Tan (Frontiers in Communication, 2025)
IntroductionThe rural tourism industry has experienced significant growth in the Mekong subregion, with women playing a crucial role in its development. This sector empowers women by enhancing their societal status and amplifying their voices.MethodsThis study examines the representation of women in rural tourism across Mekong subregion countries, focusing on visual and textual content from Destination Marketing Organization (DMOs) websites. It further assesses the alignment of these portrayals with government-led gender empowerment initiatives. Using content analysis, this research evaluates DMOs websites from the Mekong Subregion to explore comparative insights into gendered representations.ResultsThe findings reveal disparities in how men and women are portrayed: women are frequently depicted as active contributors to rural tourism within economic and socio-cultural frameworks, while men, by contrast, are more prominently featured as customers and decision-makers in political contexts. The analysis indicates that textual content downplays gender issues compared to visuals. Additionally, Vietnam and Yunnan (China) prioritize female visibility in rural tourism development, while Laos and Myanmar exhibit more conservative representations. A notable finding is the presence of indirect governmental initiatives promoting gender balance across all websites.DiscussionThe study urges policymakers and DMOs to adopt intentional strategies for equitable gender representation, ensuring women’s roles in rural tourism are both visible and empowered. It also calls for stronger alignment between tourism marketing and national gender policies in the region.